Answer:
B. y = 3x + 1
Step-by-step explanation:
We can look at the table like a bunch of values, where (x) is what is inserted into the equation, and (y) is what comes out.
Now, simply insert the (x) values into each equation and see if they work out or not.
y = (1/3)(-1) + 1 does not equal -2, meaning this equation is defunct.
y = 3(-1) + 1 = -2; y = 3(0) + 1 = 1. This must be the equation as it works for the (x) values given. You can try the other equations, but a simple look at them is all you need to prove them false.